Clinical Study and Finite Element Analysis on the Effects of Pseudo‐Patella Baja After TKA - Shenghu Jiang; Wenxing Wei; Mingyang Li; Shengliang Zhou; Yi Zeng; Bin Shen (Orthopaedic Surgery)
ABSTRACT Objective Pseudo‐patella baja (PPB) was one of the complications after total knee arthroplasty (TKA). This complication may be closely related to the occurrence of knee joint movement limitation and pain after TKA. This study aimed to investigate whether PPB affects clinical outcomes after TKA and to study the biomechanical effects of PPB after TKA. Methods This study was a retrospective case series of 462 eligible patients (563 knees). Clinical evaluation was performed using the visual analogue scale (VAS), the Hospital for Special Surgery (HSS), the Western Ontario McMaster University Osteoarthritis Index (WOMAC) scoring systems, the 5‐Level EuroQol Generic Health Index (EQ‐5D‐5L), the Forgotten Joint Score‐12 (FJS‐12), and patient satisfaction. CT and MRI scans of two healthy left knees and TKA prostheses were taken; 3D models including PPB, True patella baja (TPB), normal patella, and patella alta (PA) were created in FEA and applied load along the direction of quadriceps femoris. T‐test, Mann–Whitney U‐test, chi‐squared (χ 2) test, and analysis of variance (ANOVA) were performed using GraphPad Prism (Version 8, GraphPad Software, USA). A statistically significant difference was considered at p < 0.05 with bilateral α. Results The VAS, HSS, WOMAC, EQ‐5D‐5L, FJS‐12, and patient satisfaction scores in the PPB and TPB groups were significantly worse than those in the patella normal (PN) group (p < 0.05). The PPB group found a positive correlation between Blackburne–Peel index (BPI) and FJS‐12 score. PPB showed lower contact stress of patellofemoral joint compared to TPB when knee flexion was less than < 90° (p < 0.01), but no significant difference when flexion was more than > 90° (p > 0.05) in the finite element model with Patella baja (PB). The contact area of the patellofemoral joint tended to increase with the deepening of knee flexion, and decreased after reaching the peak value. The contact area of the patellofemoral joint tended to decrease with the increase in patellar height. There was no significant difference in the contact area of the patellofemoral joint among different patellar heights and different degrees of knee flexion (p > 0.05). Conclusion PPB after TKA may increase patellofemoral joint stress and postoperative complications like anterior knee pain.